Cas-OPRAD: a one-pot RPA/PCR CRISPR/Cas12 assay for on-site Phytophthora root rot detection - Li, Zhiting; Feng, Wanzhen; Zhu, Zaobing; Lu, Shengdan; Lin, Mingze; Dong, Jiali; Wang, Zhixin; Liu, Fuxiu; Chen, Qinghe (Frontiers in Microbiology, 2024)
Phytophthora sojae is a devastating plant pathogen that causes soybean Phytophthora root rot worldwide. Early on-site and accurate detection of the causal pathogen is critical for successful management. In this study, we have developed a novel and specific one-pot RPA/PCR-CRISPR/Cas12 assay for on-site detection (Cas-OPRAD) of Phytophthora root rot (P. sojae). Compared to the traditional RPA/PCR detection methods, the Cas-OPRAD assay has significant detection performance. The Cas-OPRAD platform has excellent specificity to distinguish 33 P. sojae from closely related oomycetes or fungal species. The PCR-Cas12a assay had a consistent detection limit of 100 pg μL -1 , while the RPA-Cas12a assay achieved a detection limit of 10 pg μL -1 . Furthermore, the Cas-OPRAD assay was equipped with a lateral flow assay for on-site diagnosis and enabled the visual detection of P. sojae on the infected field soybean samples. This assay provides a simple, efficient, rapid (< 1 hour), and visual detection platform for diagnosing Phytophthora root rot based on the one-pot CRISPR/Cas12a assay. Our work provides important methods for early and accurate on-site detection of Phytophthora root rot in the field or customs fields.